2001
DOI: 10.2190/mqf3-hgqh-9d67-m7fb
|View full text |Cite
|
Sign up to set email alerts
|

Bereavement Support Groups: Timing of Participation and Reasons for Joining

Abstract: This exploratory study investigated the experiences of a small group of people who had participated in professionally led bereavement support groups, with particular emphasis on perceptions of the appropriate timing for initial involvement with a group and the reasons for joining. The results support the need for timely group-based bereavement support. The proposition that bereavement support in the early weeks of bereavement is too early was voiced by some participants but strongly negated by others who found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 15 publications
1
19
0
Order By: Relevance
“…Picton, Cooper, Close, and Tobin (2001) found that the reasons bereavement group members gave for joining the group all involved sharing and support. These included the need for emotional support, sharing grief experiences with others who have gone through similar experiences, and a perceived absence of adequate family support.…”
Section: Social Supportmentioning
confidence: 99%
See 1 more Smart Citation
“…Picton, Cooper, Close, and Tobin (2001) found that the reasons bereavement group members gave for joining the group all involved sharing and support. These included the need for emotional support, sharing grief experiences with others who have gone through similar experiences, and a perceived absence of adequate family support.…”
Section: Social Supportmentioning
confidence: 99%
“…Further, group cohesion is associated with lower dropout rates, increased hope for the future, and higher self-esteem among group members with CG (Marmarosh, Holtz, & Schottenbauer, 2005;. Further, universality (knowledge that others share similar thoughts, problems, feelings, or have coped with similar experiences) and altruism (opportunities to support each other with advice, or help with solving problems) are common processes in bereavement groups and can facilitate group engagement and improve treatment outcomes (Brown, Brown, House, & Smith, 2008;Picton et al, 2001;Umphrey & Cacciatore, 2011).…”
Section: Social Supportmentioning
confidence: 99%
“…Self-help support groups, such as The Compassionate Friends and Bereaved Parents USA (see Resources section), are specifically designed for parents whose children have died and provide some of the best help for this prolonged grieving process. 7 These peer-led support groups provide an atmosphere in which it is possible to talk about the loss without the pressure to "get over it." Also, most parents are comforted by an environment in which others have been through a similar experience and in which they meet those who have survived this devastating loss.…”
Section: Helping During Prolonged Griefmentioning
confidence: 99%
“…Previous research on support group participation has examined predictors of participation in support groups (Levy & Derby, 1992;Picton, Cooper, Close, & Tobin, 2001). These predictors include perceived stigmatization of joining a bereavement support group (Bambauer & Prigerson, 2006;Levy & Derby, 1992) and perceived need for emotional and social support (Picton, Cooper, Close, & Tobin, 2001).…”
Section: Research On Bereavement Support Groupsmentioning
confidence: 99%
“…These predictors include perceived stigmatization of joining a bereavement support group (Bambauer & Prigerson, 2006;Levy & Derby, 1992) and perceived need for emotional and social support (Picton, Cooper, Close, & Tobin, 2001).…”
Section: Research On Bereavement Support Groupsmentioning
confidence: 99%